Tantangan Penegakan Hukum Perdata di Era Digital - Santiana Siboro; Sri Hadiningrum (Public Service and Governance Journal, 2024)
The development of science and technology has positive and negative impacts on human life. Likewise with cyberspace, one of the advances in technology, of course it is a reality that is faced with a legal metanarrative. Overcoming the ineffectiveness of legal metanarratives in addressing cyber challenges requires an innovative and comprehensive approach. Currently the world is facing changes in the industrial world which can be called the Industrial Revolution 4.0 which has a major impact on industrial life, especially in the form of rapid technological developments. The rapid development of technology has given birth to a new concept of "creative industry" which utilizes human creativity and thinking abilities. Intellectual property rights play a very important role in the creative industry, and the state recognizes the efforts and perseverance of creators/inventors in producing new innovations and minimizing the occurrence of intellectual property rights. Therefore, intellectual property must be protected legally. Violation of rights. However, in reality there are several challenges and difficulties in implementing laws related to intellectual property rights in Indonesia. This journal uses normative research methods based on legal regulations and literature studies, and considers aspects of theoretical, structural and legal explanations. The main problem that occurs in Indonesia is the low level of public awareness and education regarding intellectual property, and this problem can give rise to other problems. Intellectual property protection in Indonesia not only provides peace of mind and legal certainty for creators/inventors, but also has a psychological impact that motivates creators/inventors to continue to innovate. Indonesia will be a country that has great potential to implement Industry 4.0 because of its large workforce. The digital information era not only brings progress to industry, but can also pose challenges to labor laws. The aim of this research is to analyze labor problems due to the absence of regulations that are appropriate to the situation in the Industrial Revolution 4.0 era.